2021
DOI: 10.1080/1059924x.2021.1944416
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Exposures and Conditions among US Fishermen

Abstract: Commercial fishing is a high-risk occupation, yet there is a lack of surveillance documenting health conditions, health behaviors, and health care coverage among US fishermen. We used publicly available data sources to identify exposures and health outcomes common among fishermen. We utilized the National Institute for Occupational Safety and Health-Worker Health Charts to estimate the prevalence of general exposures, psychosocial exposures, health behaviors, and health conditions from the national surveys Nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 30 publications
(39 reference statements)
0
11
0
Order By: Relevance
“…A study of survey data from US domestic mariners also found that smoking and alcohol consumption were more common in this population 9 . Commercial fisherman were also found to have a higher prevalence of smoking and secondhand smoke exposure compared with US agricultural and all workers 13 . Globally, two different reviews found high prevalence of tobacco use and alcohol consumption among seafarers 14,15 .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…A study of survey data from US domestic mariners also found that smoking and alcohol consumption were more common in this population 9 . Commercial fisherman were also found to have a higher prevalence of smoking and secondhand smoke exposure compared with US agricultural and all workers 13 . Globally, two different reviews found high prevalence of tobacco use and alcohol consumption among seafarers 14,15 .…”
Section: Discussionmentioning
confidence: 91%
“…9 Commercial fisherman were also found to have a higher prevalence of smoking and secondhand smoke exposure compared with US agricultural and all workers. 13 Globally, two different reviews found high prevalence of tobacco use and alcohol consumption among seafarers. 14,15 Similarly, a study of French fishermen in the South Atlantic region found that a third offishermen are at risk for excessive drinking.…”
Section: Resultsmentioning
confidence: 99%
“…Fishing is strongly demanding, both physically and psychologically, implying, among the several challenges, working long hours, frequent night shifts, the unpredictability of the sea, and prolonged separation from the family [184]. Moreover, several investigations have linked the above factors to health conditions and harmful habits that are common among fishermen from different parts of the world, including the Mediterranean Sea [185], which comprise tobacco smoking, alcohol abuse, sleep deprivation, chronic stress, and so on [186,187]. Such habits are known to impact human DNA methylation [188][189][190][191], and hence must be taken into consideration when asking sampled individuals about their daily life.…”
Section: Challengesmentioning
confidence: 99%
“…Previous publications have outlined both the process of matching data 2 and the effort to explore publicly available charts to obtain commercial fishing‐specific estimates of workplace exposures, safety behaviors, health status, illnesses, and injuries, as well as working and employment conditions. 3 …”
Section: Introductionmentioning
confidence: 99%
“…RISC Fishing aims to provide a resource for PNW commercial fisheries to develop, evaluate, and inform safety initiatives by combining these sources of data into an ongoing, scalable, adaptable surveillance system and to trial the use of the system for hazard assessments and evaluations of safety and fishery management interventions. Previous publications have outlined both the process of matching data 2 and the effort to explore publicly available charts to obtain commercial fishing‐specific estimates of workplace exposures, safety behaviors, health status, illnesses, and injuries, as well as working and employment conditions 3 …”
Section: Introductionmentioning
confidence: 99%